A Review of the Development of Power Converters and Controls for Fast Charging Electric Vehicles - Wahono, Tri; Tole Sutikno; Ardiansyah; Hendril Satrian Purnama (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2025)
The review explores the development of advanced power converter topologies and control strategies for high-power fast-charging systems in electric vehicles (EVs). Fast-charging systems are crucial for EV charging infrastructure, requiring intricate design considerations and optimization procedures. Understanding hierarchical control systems and exploring power converter topologies and control technologies is essential for efficient and reliable charging. EV fast-charging systems evaluate the effectiveness of various topologies with power converters, optimizing efficiency and performance. Control strategies are crucial for the efficient and sustainable operation of fast-charging infrastructure for EVs. Integrating these strategies into fast-charging systems improves charging efficiency and grid stability, contributing to the sustainable development of EV technologies. In conclusion, the review of power converters and controls for fast-charging electric vehicles is crucial for sustainable transportation infrastructure. Fast charging technology for EVs is advancing rapidly, enhancing charging performance and promoting sustainable transportation. Innovative charger designs and control techniques are crucial for efficient charging. However, the review acknowledges limitations due to the evolving landscape of fast-charging infrastructure and the complexities of grid integration. Future research should focus on overcoming challenges, advancing technologies, and integrating renewable energy sources, energy storage solutions, and grid connectivity. This will contribute to the widespread adoption of electric mobility.